A novel treatment method of PVC-medical waste by near-critical methanol: Dechlorination and additives recovery. (October 2018) - Qi, Yingying; He, Jiahuan; Li, Yifan; Yu, Xuan; Xiu, Fu-Rong; Deng, Yuehua; Gao, Xiang
Graphical abstract: Highlights: We report a novel NCM process for treatment of PVC-medical waste. Dechlorination and additives recovery were achieved simultaneously. Dechlorination efficiency exceeded 90% at 250 °C. DBP, DOP, and DMP were efficiently recovered from TFT by the NCM process. Methyl palmitate and methyl stearate were efficiently recovered from SCFU. Abstract: Before PVC-medical waste is subjected to a waste-to-energy recovery process, the dechlorination and the recovery of additives such as plasticizer, stabilizer, and lubricant are quite important and attractive. In this work, a novel process was developed for the dechlorination and the recovery of additives from PVC-medical waste such as tube for transfusion (TFT) and sample collector for urine (SCFU) by using near-critical methanol (NCM). Reaction temperature, solid-to-liquid ratio, and reaction time have significant effect on the dechlorination of TFT and SCFU in NCM. The order of dechlorination efficiency of the samples at the same reaction conditions is as follows: TFT > Pure PVC > SCFU. When reaction temperature was controlled at 250 °C (solid-to-liquid ratio of 1:10 g/mL, reaction time of 60 min), the dechlorination efficiency reached 90%. Plasticizer such as dibutyl phthalate (DBP), dioctyl phthalate (DOP), and dimethyl phthalate (DMP) could be efficiently extracted and recovered from TFT at 250 °C by the NCM process. The recovery efficiency of DBP, DOP, and DMP decreased significantly with increasing temperature due to the further decomposition and other secondary reactions. High level of hexadecanoic acid methyl ester and octadecanoic acid methyl ester can be obtained from SCFU at 250 °C by the NCM process because of the esterification between methanol and hexadecanoic acid/octadecanoic acid, which are the important stabilizers and lubricants generally used in rigid PVC. It is noteworthy that methanol can be circulated and reused in the NCM process. This result showed that the NCM process was beneficial for both the dechlorination and the additives recovery from PVC-medical waste, and had a widespread application prospect for the waste management of PVC wastes.